Christian Theology at the University: On the threshold or in the margin? - Mouton, Elna (HTS teologiese studies, 2008)
The essay discusses challenges regarding the position and role of Christian Theology in twenty-first century university contexts. Questions asked include the following: How will a theology that is oriented to (Reformed) Christian Theology develop itself at universities worldwide, within contexts of secularisation and globalisation? What important strategic choices will it have to make? It is argued that answers to such questions inter alia relate to how Christian Theology responds to three crucial choices: (1) Being truthful to its biblical orientation and calling; (2) Accounting critically for its position on the threshold of interdisciplinary and interreligious dialogue; and (3) Being connected to the life stories of people.